Negotiating Integrity and Self-Identity: Transforming Authentic Leadership Through OBE-Based Reflective Learning in Educational Management Students - Enung Hasanah; Zultiyati Zultiyati; M. Ikhsan Al Ghazi (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study aims to explore the process of identity transformation and psychological dynamics of college students in leadership development through a Reflective Outcomes-Based Education (OBE) intervention. Using a qualitative research design, the study involved 11 participants who provided in-depth data through a structured reflection instrument. Results indicate that authentic leadership development is triggered by two main interrelated processes. First, an intense value negotiation dynamic emerges, in which participants grapple with the balance between personal ego and collective interests to build integrity through transparency and acceptance of their own vulnerability. Second, this process culminates in significant self-transformation, marked by the deconstruction of old understandings and the reconstruction of identity from a people-pleasing mentality to a principled leadership one. The study concludes that the reflective intervention within the OBE framework not only increases self-awareness but also builds resilience to external pressures through stronger self-mastery.